OCCURRENCE OF INTESTINAL MICROSPORIDIA INFECTION AMONG HIV/AIDS PATIENTS ATTENDING GENERAL AND DIVINE MERCY HOSPITAL MINNA, NIGER STATE - Ubanwa, E. D; Nnamani, S. M; Benjamin, G, Y (Global Journal of Medical and Health Science, 2023)
Microsporidia infection may be asymptomatic in immunocompetent individual; however, can be severe and disseminated among HIV/AIDs patients, children less than five years, elderly, immunocompromised patients. Of 748 samples was collected from HIV - and HIV/AIDS tested for microsporidia using Giemsa stain, 11(1.47%) were positive. Stool hard 9(2.14%) and urine 2(1.01%) all from HIV/AIDS while HIV - show no positive cases at p < 0.05 a significant difference was recorded. Age and sex, highest was within 26 - 35 years (3.29%) female hard highest (1.84%). Predisposing factor, cases of hard (5.48%), while pipe born water (0.00%). It has proved that the parasite is highly associated with diarrhoea and among immunocompromised patient as an opportunistic infection. Immunocompromised patient, elderly, and organ transplant individual have to improve on both personal and environmental hygiene.